2019
DOI: 10.1001/jamanetworkopen.2019.1286
|View full text |Cite
|
Sign up to set email alerts
|

Association of Deferred vs Immediate Cord Clamping With Severe Neurological Injury and Survival in Extremely Low-Gestational-Age Neonates

Abstract: This cohort study compares neonatal outcomes after deferred cord clamping vs immediate cord clamping in extremely low-gestational-age neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
2
18
0
1
Order By: Relevance
“…Meta-analyses of more recent studies have shown DCC, compared with early cord clamping (ECC), is associated with higher haemoglobin and haematocrit, higher blood pressure, fewer blood transfusions, reduced intraventricular haemorrhage, and decreased hospital mortality 3 4. A very large population-based study showed reduced severe neurological injury5 in infants 22–28 weeks’ gestational age (GA) receiving DCC.…”
mentioning
confidence: 99%
“…Meta-analyses of more recent studies have shown DCC, compared with early cord clamping (ECC), is associated with higher haemoglobin and haematocrit, higher blood pressure, fewer blood transfusions, reduced intraventricular haemorrhage, and decreased hospital mortality 3 4. A very large population-based study showed reduced severe neurological injury5 in infants 22–28 weeks’ gestational age (GA) receiving DCC.…”
mentioning
confidence: 99%
“…Since survival with good neurodevelopmental outcomes is a goal for all neonates, a simple interventionlike DCC-that decreases the risk of death, severe intraventricular hemorrhage, and periventricular leukomalacia is desirable. However, while the study by Lodha et al6 demonstrated decreased severe…”
mentioning
confidence: 89%
“…Despite evidence from the study by Lodha et al 6 and evidence from the 18 RCTs 4 demonstrating improved survival in preterm infants with DCC, clinicians may continue to be more comfortable immediately taking over the resuscitation process in favor of waiting out a minute of uncertainty.…”
mentioning
confidence: 99%
See 2 more Smart Citations